THE INFLUENCE OF WORK CULTURE AND PROFESSIONAL DEVELOPMENT ON TEACHER QUALITY AND ITS IMPACT ON LEARNING QUALITY AT PUBLIC ELEMENTARY SCHOOLS IN SAKETI DISTRICT, PANDEGLANG REGENCY - Inayati, Tatu E.; Rustandi, Tata; Permana, Angrian (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to explore the influence of professional ethics and work discipline on teacher performance, as well as to examine the mediating role of teacher professionalism among public elementary school teachers in Banjar District, Pandeglang Regency. The primary focus of the study is to identify the direct and indirect effects of these variables on improving teacher performance. The research method employed a quantitative approach using regression analysis techniques using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The study sample included 100 respondents drawn from a population of 163 public elementary school teachers, providing an empirical overview of the relationships between the variables. The results indicate that professional ethics has a positive and significant effect on teacher professionalism and on teacher performance. Similarly, work discipline has been shown to have a significant positive effect on both teacher professionalism and teacher performance. Furthermore, teacher professionalism itself has a positive and significant effect on teacher performance. The mediation test also demonstrated that professional ethics and work discipline significantly influence teacher performance through teacher professionalism. These findings emphasize the importance of implementing professional ethics and work discipline as key factors driving teacher professionalism. Improving professionalism can ultimately strengthen teacher performance, so policies and evaluations are needed that support efforts to improve the quality of education.